The Effect Of A Training Program On The Autonomy Of Old Women - Esselma, Nouria; bensikaddour, habib (revue des sciences et technologie des activités physique et sportive, 2018)
Older people with walking difficulties are particularly fragile and at risk for functional decline, To retain as long as possible functional independence, this work aims to provide a physical program tailored to improve walking and balance for the elderly (over 65 years ) and Predict the influence of physical training on them so that we can to help this population group maintain or recover certain motor capacity . In order to help them perform daily activities and be independent without assistant need. 20 elderly with an average age of 79.6 years .institutionalized in a geriatric structure were chosen and divided into two groups; The experimental group (10 women) participated in a physical program suitable for 12 weeks with an average of 3-hour sessions per week. Both groups (experimental and control) have participated in pre-test and post-test. The Results according to the research variables were characterized by significant differences. The training has improved static balance and different gait parameters
Keywords: elderly, physical training, training program, autonomy